(untitled) (Hematology Meeting Reports, 2009)
Peripheral T/NK-cell lymphomas (PTCL) comprise a rare and heterogeneous group of malignancies accounting for approximately 10-15% of all non- Hodgkin’s lymphomas (NHL) in Western countries. PTCL in general are characterized by an aggressive course and most studies revealed the T-cell phenotype as a negative prognostic marker.1-4 The international prognostic index (IPI) and T-cell specific prognostic index (PIT) have shown prognostic value in PTCL determining the outcome of patients with nodal peripheral T-cell lymphomas.5-8